Reduced retinal microvascular density in women with coronary microvascular dysfunction: A pilot study - Sakshi Shiromani; Ahmed AlBadri; Aaron Lindeke-Myers; Arielle Schwartz; Nishant Vatsa; Esha Dave; Fauzia Rashid; Nieraj Jain; Puja K. Mehta (American Heart Journal Plus)
Objective: To compare retinal microvascular density among women with ischemia with no obstructive coronary artery disease (INOCA) with and without coronary microvascular dysfunction (CMD). Design: Cross-sectional study. Setting: Patients with myocardial INOCA often have CMD, possibly indicating systemic vascular dysfunction. While retinal microvasculature relates to many cardiovascular risk factors, its link with CMD remains unknown. Participants: Women with INOCA (N = 18) and coronary function testing were enrolled and classified into CMD and non-CMD groups, with CMD defined as coronary flow reserve (CFR) <2.5 in response to adenosine. Interventions: Participants underwent retinal optical coherence tomography angiography for noninvasive imaging of the retinal microvasculature. Main outcome measures: Vessel density, perfusion density, and area, perimeter, and circularity of the foveal avascular zone (FAZ). Non-parametric statistics were used for comparisons. Results: Mean age was 54.7 (SD 12.5) years. The CMD (N = 11) and non-CMD (N = 7) groups were balanced with respect to age, BMI, systemic diseases including diabetes, hypertension, and hyperlipidemia, and medications. Those with CMD had a lower retinal vessel density [20.9 (0.7) vs 21.6(0.8), p = 0.006] and lower inner perfusion density [38.5 (1.6) vs 41.2 (0.8), p = 0.006] as compared to those without CMD. There were no differences in the FAZ area, perimeter, or circularity. Conclusions: In this study of women with INOCA, those with CMD showed lower retinal microvascular and perfusion densities than those without CMD. Direct, non-invasive retinal imaging is feasible, affordable, and may reflect coronary microvascular function in INOCA patients. A larger study, including men, is needed to confirm these findings.